P393 Clinical spectrum and molecular characterization of Rhytidhysteron spp. (now Gloniopsis) from India. (20th September 2022) - Ahmad, Haseen; Kaur, Harsimran; Gupta, Parakriti; Shankaranarayana, Shamanth; Agnihotri, Sourav; Mehta, Preeti; Salve, Suneeta; Yoganand, Raksha; Tarai, Bansidhar; Tejashree, A; Hemashettar, Basavaraj; Balajee, G; et al.
Abstract: Poster session 3, September 23, 2022, 12:30 PM - 1:30 PM: Objective: Rhytidhysteron spp. are emerging dematiaceous fungi implicated in subcutaneous infections in immunocompromised as well as immunocompetent individuals. Diagnosis of Rhytidhysteron spp is delayed owing to non-sporulation and misidentification. The present study was conducted to characterize Rhytidhysteron spp. isolated from India by molecular techniques. Method: We retrieved a total of eight isolates of Rhytidhysteron spp from our National Culture Collection for Pathogenic Fungi (NCCPF) that were received from various centers across India. Colony morphology on Sabouraud's dextrose agar (SDA) and potato dextrose agar (PDA) was recorded. Molecular identification was performed by sequencing internal transcribed spacer (ITS) and 28 s region of rDNA. Phylogenetic tree was constructed using the Neighbor-Joining method along with sequences of standard strains retrieved from the NCBI database. Results: Rhytidhysteron spp was confirmed by sequencing from cutaneous specimens of eight cases. Six patients were immunocompetent while two were post-renal transplant recipients. Phenotypic features on SDA and PDA revealed growth of greyish-black mycelia on the obverse with black pigmentation on reverse after 7 days of incubation. On microscopic examination of lactophenol cotton blue mount, only dematiaceous septate hyphae without any spores were noted. On phylogenetic analysis of 28 s region, four of our isolates were closely clustered with Gloniopsis calami (Fig.1b), whereas two isolates with G. pneumonia and one each with G. percutanea, and Gloniopsis spp. (Fig.1b). On ITS phylogeny, the same four isolates closely clustered with G. calami (Fig.1a) as in 28 s region, one each isolate clustered with G. pneumonia, and G. percutanea while two isolates formed a separate clade with Rhytidhysteron rufulum (Fig.1a). Conclusion: This fungus is often difficult to identify due to lack of sporulation making morphological identification challenging. Therefore, molecular sequencing is a must for its identification. However, identification using the sequence of ITS and 28 s rDNA does not clearly correlate. Hence to confirm the identity additional genes needs to be sequenced and analyzed.